Metabolomic patterns and alcohol consumption in African Americans in the Atherosclerosis Risk in Communities Study(1)(2)(3) - Zheng, Yan (American Society for Nutrition, 2014)
Background: Effects of alcohol consumption on health and disease are complex and involve a number of cellular and metabolic processes. Objective: We examined the association between alcohol consumption habits and metabolomic profiles. Design: We conducted a cross-sectional study to explore the association of alcohol consumption habits measured by using a questionnaire with serum metabolites measured by using untargeted mass spectrometry in 1977 African Americans from the Jackson field center in the Atherosclerosis Risk in Communities Study. The whole sample was split into a discovery set (n = 1500) and a replication set (n = 477). Alcohol consumption habits were treated as an ordinal variable, with nondrinkers as the reference group and quartiles of current drinkers as ordinal groups with higher values. For each metabolite, a linear regression was conducted to estimate its relation with alcohol consumption habits separately in both sets. A modified Bonferroni procedure was used in the discovery set to adjust the significance threshold (P < 1.9 × 10(−4)). Results: In 356 named metabolites, 39 metabolites were significantly associated with alcohol consumption habits in both discovery and replication sets. In general, alcohol consumption was associated with higher levels of most metabolites such as those in amino acid and lipid pathways and with lower levels of γ-glutamyl dipeptides. Three pathways, 2-hydroxybutyrate-related metabolites, γ-glutamyl dipeptides, and lysophosphatidylcholines, which are considered to be involved in inflammation and oxidation, were associated with incident cardiovascular diseases. Conclusions: To our knowledge, this is the largest metabolomic study thus far conducted in nonwhites. Metabolomic biomarkers of alcohol consumption were identified and replicated. The results lend new insight into potential mediating effects between alcohol consumption and future health and disease.